Orang Haria and Marriage Customs: The Reality of Socio-cultural Order in the Maluku Archipelago - Alfons, Christwyn Ruusniel; Titaley, Elsina (KnE Social Sciences, 2024)
Maluku is an archipelagic region consisting of both large and small islands surrounded by the ocean. The community interaction dynamics on and between these islands are shaped by the knowledge or mindsets based on each community’s cultural background or traditional customs, which are institutionalized within every individual and within the collective community of its adherents. Specifically, marriage customs, whether it involves payment of a dowry or traditional legitimization, integrates two individuals with different identity backgrounds into the social environment on a micro-scale (family/mataruma) and a macro scale (village/community). The people of Haria identify themselves as part of Negeri Haria, one of the traditional villages on Saparua Island, Maluku, which has meaningful marriage traditions aimed at establishing social and cultural order. These marriage customs signal to family members and ancestors about the marriage events of descendants, visible from the traditional process of introducing a wife, whether from within or outside Negeri Haria, and the obligations of a man who marries and takes a daughter from Negeri Haria to merge with his identity (family/original village). The various conditions include kain berkat (negeri wealth) meja kaweng, marriage dowry payment, and hatu mata. Additionally, there are traditions of changing the surname of a child born out of wedlock (child reallocation) or adopting someone else’s anak (arken anak). The young generation of Negeri Haria, generally needs more precise knowledge about marriage customs to form social order for newly established households. This writing aims to reveal the objective reality of the community’s oral traditions in written form, preserved for cultural conservation purposes. The reality was discovered using qualitative research, such as observation and interview methods. Hence, efforts to preserve the cultural values of this indigenous community involve tracing stories from traditional leaders who possess the knowledge and perform the ritual processes of marriage customs. Keywords: Orang Haria, marriage customs, socio-cultural regularities